Analysis of Supporting and Inhibiting Factors in the Integration of Character Education in Akidah Akhlak Subjects at MIN 11 Aceh Tenggara - Harpan Reski Mulia (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Jember, 2022)
This paper aims to explore the supporting and inhibiting factors in the effort to integrate character education in akidah akhlak subjects at MIN 11 Aceh Tenggara. This study uses a qualitative method with a narrative approach and data collection techniques of interview, observation, and documentation; then, the data is analyzed using the methods developed by Miles and Huberman, namely data reduction, data presentation, and data verification. This study shows that the supporting factor for integrating character education in aqidah moral learning at MIN 11 Aceh Tenggara is the availability of learning media in the form of focus and Madrasah residents who work together to supervise all students, both outside and inside the Madrasah environment. The inhibiting factors are the limitations of Madrasah infrastructure in the form of no mosque or prayer room, family support, and social media and games that have an influence on student character. Tulisan ini bertujuan untuk mengeksplorasi faktor pendukung dan penghambat dalam upaya pengintegrasian pendidikan karakter pada mata pelajaran akidah akhlak at MIN 11 Aceh Tenggara. Penelitian ini menggunakan metode kualitatif dengan pendekatan naratif dan teknik pengumpulan data wawancara, observasi dan dokumentasi, kemudian data dianalisis dengan metode yang dikembangkan Miles dan Huberman, yaitu reduksi data, penyajian data dan verifikasi data. Penelitian ini menunjukkan bahwa, faktor pendukung pengintegrasian pendidikan karakter dalam pembelajaran Akidah Akhlak MIN 11 Aceh Tenggara adalah kesedian media pembelajaran berupa infocus dan warga Madrasah yang bersinergi untuk mengawasi semua siswa, baik di luar maupun di dalam lingkungan Madrasah. Adapun faktor penghambatnya adalah keterbatasan prasarana Madrasah berupa tidak ada Masjid atau musala, dukungan keluarga, dan media sosial dan game memberikan pengaruh terhadap karakter siswa.